2021
DOI: 10.3390/ijms222111578
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomolecules in the Pathogenesis of Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) is one of the most common metabolic diseases in pregnant women. Its early diagnosis seems to have a significant impact on the developing fetus, the course of delivery, and the neonatal period. It may also affect the later stages of child development and subsequent complications in the mother. Therefore, the crux of the matter is to find a biopredictor capable of singling out women at risk of developing GDM as early as the very start of pregnancy. Apart from the well-known mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 179 publications
(307 reference statements)
0
26
1
Order By: Relevance
“…For these reasons, WWOX targeting may prove to be more effective. Leptin expression, another one of adipocytokines, controlling insulin-dependent glucose transport to adipocytes [ 91 ] was found to be hypoxia-inducible [ 92 ], which is stimulated in adipose tissue [ 93 ] and placenta [ 94 ] through HIF1. Hypoxia-inducible factor is also responsible for upregulation of visfatin mRNA expression [ 95 ] in the fat tissue of obesity patients and significantly higher levels of visfatin was observed in the population of obese T2DM patients compared to healthy subjects [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, WWOX targeting may prove to be more effective. Leptin expression, another one of adipocytokines, controlling insulin-dependent glucose transport to adipocytes [ 91 ] was found to be hypoxia-inducible [ 92 ], which is stimulated in adipose tissue [ 93 ] and placenta [ 94 ] through HIF1. Hypoxia-inducible factor is also responsible for upregulation of visfatin mRNA expression [ 95 ] in the fat tissue of obesity patients and significantly higher levels of visfatin was observed in the population of obese T2DM patients compared to healthy subjects [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…ANGPTL8, a 22 kDa protein, is secreted by the liver and adipose tissue and plays important roles in glucose homeostasis, lipid metabolism and inflammation [ 50 ]. Today there is a discussion on whether ANFPTL8 is able to induce pancreatic beta-cell proliferation and increase insulin secretion, although the consensus is that it is not capable of such actions [ 10 ]. Many studies have shown that ANGPTL8 correlates negatively with HDL-C levels and positively with triglyceride levels, making it a crucial modulator of lipid metabolism [ 51 ].…”
Section: Adipokines In Maternal Circulationmentioning
confidence: 99%
“…Although some key pathophysiological mechanisms in GDM have been extensively described to date, it is in the last few decades that several adipokines have shown some involvement in the metabolic alterations underlying GDM. Today, there are excellent reviews of the role of adipokines in GDM, with special focus on the maternal circulating profile [ 8 , 9 , 10 , 11 ]. However, it is in recent years that more progress has been made in the study of their expression in visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), placenta, and their concentrations in the umbilical circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to placental hormones such as human placental lactogen, progesterone, cortisol, growth hormone, and prolactin, pregnancy is linked to physiological IR, especially in the second and third trimester of pregnancy [ 43 , 44 ]. Recently, the role of leptin stimulating IR and the inhibitory role of adiponectin have been emphasized [ 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Pregnancy As a Window For The Development Of Metabolic Diseasesmentioning
confidence: 99%